Oxidative dissolution of chalcopyrite by Acidithiobacillus ferrooxidans analyzed by electrochemical impedance spectroscopy and atomic force microscopy - Bevilaqua, D.; Diez-Perez, I; Fugivara, Cecilio Sadao [UNESP]; Sanz, F.; Benedetti, Assis Vicente [UNESP]; Garcia, O. (Elsevier B.V., 2004)
The microbiological leaching of chalcopyrite (CuFeS2) is of great interest because of its potential application to many CuFeS2-rich ore materials. However, the efficiency of the microbiological process is very limited because this mineral is one of the most refractory to bacterial attack. Knowledge of bacterial role during chalcopyrite oxidation is very important in order to improve the efficiency of bioleaching operation. The oxidative dissolution of a massive chalcopyrite electrode by Acidithiobacillus ferrooxidans was evaluated by electrochemical impedance spectroscopy (EIS) and atomic force microscopy (AFM). A massive chalcopyrite electrode was utilized in a Tait-type electrochemical cell in acid medium for different immersion times in the presence or absence of bacterium. The differences observed in the impedance diagrams were correlated with the adhesion process of bacteria on the mineral surface. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Acidithiobacillus ferrooxidans; electrochemical impedance spectroscopy (EIS); atomic force microscopy